2006
DOI: 10.1136/vr.158.23.804
|View full text |Cite
|
Sign up to set email alerts
|

High levels of corticosterone in feather‐plucking parrots (Psittacus erithacus)

Abstract: These results indicate that feather-plucking parrots have higher baseline corticosterone levels and suggest that they do indeed have higher chronic stress levels than non-featherplucking parrots. Many factors could contribute to this stress: for example, housing conditions, lack of interactions with conspecifics, the effect of hand-rearing versus parent-rearing, environmental enrichment and physical health. Such variables need to be investigated systematically in order to determine the causal factors. This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
14
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 1 publication
6
14
0
Order By: Relevance
“…Our results confirm the findings of Owen & Lane (2006), which showed higher CM in the droppings of FDB-HR parrots than in control parrots. To the best of our knowledge, the paper of Owen & Lane (2006) is the only study comparing the CM excretion in droppings of FDB and non-FDB African grey parrots (261 ng/g and 75 ng/g, respectively). Our results confirm these observations in terms of significant differences between FDB-HR and H-HR parrots, but the magnitude of the values measured in our study was more than 6 times higher than those observed by Owen & Lane (2006).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results confirm the findings of Owen & Lane (2006), which showed higher CM in the droppings of FDB-HR parrots than in control parrots. To the best of our knowledge, the paper of Owen & Lane (2006) is the only study comparing the CM excretion in droppings of FDB and non-FDB African grey parrots (261 ng/g and 75 ng/g, respectively). Our results confirm these observations in terms of significant differences between FDB-HR and H-HR parrots, but the magnitude of the values measured in our study was more than 6 times higher than those observed by Owen & Lane (2006).…”
Section: Discussionsupporting
confidence: 91%
“…It is well known that chronic stress is involved in behavioral disorders in captive parrots (Ferreira et al, 2015;Owen & Lane, 2006). In vertebrates, the front-line hormones for overcoming stressful situations are β-endorphin, glucocorticoids and catecholamines (Ayala et al, 2012;Johnstone, Reina & Lill, 2012;Livingston, 2010;Schmidt et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Dickcissels (Spiza americana) with corticosterone concentrations ∼6 ng/g in the absence of stressor agents, increased their values to ∼102 ng/g when they where subject to a stressor agent (Kimberly et al, 2003). African Grey Parrots (Psittacus erithacus) exhibited low corticosterone concentration values under normal conditions (∼75 ng/g), but showed three times higher values when stressed by feather-plucking (∼265 ng/g; Owen and Lane, 2006). Spotted Owls (Strix occidentalis) also responded to stressor agents, with low corticosterone concentration values in preserved areas (∼20-60 ng/g) and almost four times higher concentration values in disturbed areas (∼98-110 ng/g; Wasser et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Intensifying preening can be a result of excessive self-comforting linked with chronic stress (Garner and others 2003); this is supported by elevated corticosterone levels in FDB cases (Owen and Lane 2006). Identifying stressors is aided by taking a comprehensive history.…”
mentioning
confidence: 99%